2012
DOI: 10.3168/jds.2011-5198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial resistance, and molecular characterization of methicillin-resistant Staphylococcus aureus from bulk tank milk of dairy herds

Abstract: It was the objective of the study to estimate the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in bulk tank milk from German dairy herds and to characterize isolates from bulk tank milk with respect to their Staph. aureus protein A (spa) and staphylococcal cassette chromosome mec (SCCmec) type, their phenotypic antimicrobial resistance and resistance-resp. virulence-associated genes using broth microdilution and a microarray for Staph. aureus. Bulk tank milk samples (25 mL) were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 23 publications
10
63
5
1
Order By: Relevance
“…Although MRSA is comparatively rare in food, dairy milk might be one of the possible sources of MRSA because of wide use of antimicrobials for the treatment of mammary infections in cattle (2,22,24). The presence of MRSA strains in bovine milk has been reported in various countries, including Italy, Germany, England, and Turkey, and these data are consistent with in the results of the present study (2, 22, 35, 38).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although MRSA is comparatively rare in food, dairy milk might be one of the possible sources of MRSA because of wide use of antimicrobials for the treatment of mammary infections in cattle (2,22,24). The presence of MRSA strains in bovine milk has been reported in various countries, including Italy, Germany, England, and Turkey, and these data are consistent with in the results of the present study (2, 22, 35, 38).…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were reported in Turkey (38): 17% of 93 S. aureus isolates were MRSA. The 1.8% prevalence of MRSA in our samples (7 of 383 samples) is comparable with the 2.3% prevalence reported in England (35) and Germany (22).…”
Section: Discussionsupporting
confidence: 72%
“…Para el caso de unos pocos aislamientos de S. aureus resistentes a los antibióticos β-lactámicos obtenidos en este estudio, el hallazgo podría asociarse a la presencia de algunas cepas del grupo del S. aureus resistente a meticilina (SARM), los cuales deben considerarse resistentes a todas las penicilinas, cafalosporinas, cefemas y otros β-lactámicos. Sin embargo, existen pocos reportes de SARM en este grupo de animales y en su leche (33)(34)(35)(36).…”
Section: Discussionunclassified
“…In a recent study in Germany, the prevalence of MRSA infection among dairy herds, based on testing of bulk tank milk samples, was 4.4 % (Kreausukon et al, 2012), and regional studies performed in southern Germany reported a comparable, while slightly lower, prevalence of 2.2 % . Similarly, studies on milk samples from dairy herds in southwest Germany indicated a prevalence of between 5.1 and 16.7 %, and MRSA was also isolated from bulk tank milk samples from the farms under investigation .…”
Section: Staphylococcus Aureus Including Meticillin-resistant Staphymentioning
confidence: 92%